The Relevance of the Tahfidz Program in Shaping Students Qur'anic Morality in the Era of Modernization at Islamic Boarding Schools - Siregar, Mansur Ali Hanafi; Tumiran, Tumiran (Al-Fikru: Jurnal Ilmiah, 2025)
This research departs from the challenges of modernization that increasingly affect the moral and spiritual values of the younger generation, including in the context of Islamic education. Many young people experience an identity crisis and moral decline due to the influence of globalization and social media. The purpose of this study is to examine the relevance of the tahfidz al-Qur'an program in shaping the Qur'anic morals of students at the Sulaimaniyah Islamic Boarding School in Medan, as a response to these challenges. The method used is descriptive qualitative approach, with data collection through interviews, observation, and documentation. The results showed that the tahfidz program in this pesantren is effective in shaping Qur'anic morals through strategies that include exemplary ustaz, character-based assessment, habituation to worship, and strengthening the values of piety and istiqamah. However, challenges arise both from internal factors, such as the pressure of memorization targets, and external, in the form of the influence of modernization and technology. The implication of this study is the importance of a comprehensive approach in the management of tahfidz program, focusing on character development, moral resilience, and wise use of technology in supporting tahfidz education.